(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article is dedicated to humanistic features of prose anthology «The Song of All Songs» by J. Burg, the Ukrainian author who wrote in other language. They are analyzed through the prism of artistic comprehension of social, religious, cultural, political, historical realities of Jewish life in the XX ct. in different states. The subject of a particular attention is the Holocaust theme as a main theme of the anthology which forms the plot.